Gross haematuria associated with penetration of an inferior vena cava filter into the right renal collecting system. (6th March 2015) - Cusano, Antonio; Rosenberg, David; Haddock, Peter; Meraney, Anoop
Abstract : Inferior vena cava (IVC) filters are a viable alternative for patients with venous thromboembolic disease for whom standard anticoagulation therapy is contraindicated. Rare complications associated with their use, however, include misplacement and IVC penetration. We report a case of a 63-year-old woman who developed gross haematuria following IVC filter penetration into both the right renal collecting system and renal pelvis, for which open caval removal and reconstruction was required. This is an unusual case of IVC filter penetration causing symptomatic haematuria and requiring surgical intervention.